2021
DOI: 10.2337/dc20-2641
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss by Low-Calorie Diet Versus Gastric Bypass Surgery in People With Diabetes Results in Divergent Brain Activation Patterns: A Functional MRI Study

Abstract: OBJECTIVE Weight loss achieved with very-low-calorie diets (VLCDs) can produce remission of type 2 diabetes (T2D), but weight regain very often occurs with reintroduction of higher calorie intakes. In contrast, bariatric surgery produces clinically significant and durable weight loss, with diabetes remission that translates into reductions in mortality. We hypothesized that in patients living with obesity and prediabetes/T2D, longitudinal changes in brain activity in response to food cues as measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…Applied to bariatric surgery, most studies demonstrate normalization of impaired activity and/or connectivity patterns in the obese (before surgery) towards patterns observed in lean controls (VSG [ [155] , [156] , [157] , [158] ], RYGB [ 155 , [159] , [160] , [161] , [162] , [163] , [164] , [165] ]). In one study presurgical functional connectivity predicted the magnitude of weight loss induced by VSG [ 166 ], and another study found that activation of cortical areas involved in inhibitory control was significantly greater after RYGB compared to VSG [ 155 ].…”
Section: Bariatric Surgery Changes Gut-brain Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Applied to bariatric surgery, most studies demonstrate normalization of impaired activity and/or connectivity patterns in the obese (before surgery) towards patterns observed in lean controls (VSG [ [155] , [156] , [157] , [158] ], RYGB [ 155 , [159] , [160] , [161] , [162] , [163] , [164] , [165] ]). In one study presurgical functional connectivity predicted the magnitude of weight loss induced by VSG [ 166 ], and another study found that activation of cortical areas involved in inhibitory control was significantly greater after RYGB compared to VSG [ 155 ].…”
Section: Bariatric Surgery Changes Gut-brain Communicationmentioning
confidence: 99%
“…One significant issue for many of the above studies is the inability to distinguish the direct effects of the surgery from the resulting weight loss. Only one study compared low-calorie diet vs. gastric bypass surgery in order to distinguish between surgery-specific and weight loss-specific effects [ 161 ]. In a cohort of mostly female patients with obesity and type-2 diabetes, fMRI scans capturing the response to food cues in the fed versus fasted state were conducted before and 4 weeks after either very low calorie diet (VCLD) or RYGB.…”
Section: Bariatric Surgery Changes Gut-brain Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, increasing studies have used fMRI to observe changes in brain activity in response to food cues in an effort to gain a deeper understanding about the mechanisms of BS. RYGB resulted in different brain responses compared with a very‐low‐calorie diets in clinical trials: RYGB resulted in a more active homeostatic appetite system, as well as reduced neural activation in response to food cues in cognitive control regions and responsiveness to food cues in the reward center of the brain, 192 resulting in favorable changes in food rewards and preferences 10,193 . Another study, by utilizing functional brain imaging, reported that brain responses to high‐fat milkshake cues normalized at 1 year following RYGB in obese participants 194 .…”
Section: Mechanisms Of Bariatric Surgerymentioning
confidence: 99%
“…For example, topiramate may cause increased pulse and blood pressure in certain patients and increase the risk of oral clefts in infants when taken by pregnant women; liraglutide has obvious gastrointestinal side effects, such as nausea, vomiting, diarrhea, and an increased risk of pancreatitis 8 . Moreover, short‐term weight control is easily achieved by the means described, but it is prone to weight regain 9,10 . There are certain advantages in maintaining long‐term weight loss for bariatric surgery (BS) in severely obese patients 7,11 .…”
Section: Introductionmentioning
confidence: 99%